2007
DOI: 10.1038/sj.npp.1301354
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Loss of Hippocampal LTD and Cognitive Flexibility in a Genetic Model of Hyperdopaminergia

Abstract: Dopamine-mediated neurotransmission has been implicated in the modulation of synaptic plasticity and in the mechanisms underlying learning and memory. In the present study, we tested different forms of activity-dependent neuronal and behavioral plasticity in knockout mice for the dopamine transporter (DAT-KO), which constitute a unique genetic model of constitutive hyperdopaminergia. We report that DAT-KO mice exhibit slightly increased long-term potentiation and severely decreased long-term depression at hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 43 publications
4
70
0
2
Order By: Relevance
“…M Bellesi and F Conti of hippocampal LTD (Morice et al, 2007). On these bases, it has been suggested that LTD could have a key role in modulating cognitive flexibility as well as in other complex cognitive functions (Morice et al, 2007;Nicholls et al, 2008).…”
Section: Ly379268 Blocks Cef-induced Ppi Impairmentmentioning
confidence: 99%
“…M Bellesi and F Conti of hippocampal LTD (Morice et al, 2007). On these bases, it has been suggested that LTD could have a key role in modulating cognitive flexibility as well as in other complex cognitive functions (Morice et al, 2007;Nicholls et al, 2008).…”
Section: Ly379268 Blocks Cef-induced Ppi Impairmentmentioning
confidence: 99%
“…The involvement of both dopamine receptors families with learning and memory is widely reported for working memory [3], spatial learning [3,6], aversive memory [7], reward-related learning [8] and cognitive flexibility [9]. In particular, impairment in object recognition has been induced by D2 activity suppression due to haloperidol IP injection [10], by D1 activity suppression trough http://dx…”
Section: H I G H L I G H T Smentioning
confidence: 99%
“…Furthermore, mice lacking D2 receptors do show memory consolidation deficits [15]. On the other hand, animals with high levels of synaptic DA, namely knockout mice for the DA transporter (DAT-KO), show impairment in the Morris water maze task [9], and also impairment of spatial memory in the Y-maze [16]. These animals presented, however, less immobility time in the forced swimming task [17], and exhibited an increase in locomotion, reversed by D2 receptor blocking [17].…”
mentioning
confidence: 99%
See 2 more Smart Citations